Liberalism in the Islamic World and its influence in the Malay Archipelago: Model in Indonesia - Abbas Mansur Tamam (International Journal of Nusantara Islam, 2013)
Liberalism means here Orientalist attempt to attract even Islam conformity with the principles of Western liberalism in form and substance. Hence Zhardha in the Islamic world have to do Orientalism, which under his leadership became the U.S. currently wants Islam that corresponds to the values of modernity and secularism and Western liberalism. And this phenomenon coincides appearance in the Islamic world with its appearance Malay archipelago and Indonesia to face particular Alholanda since colonial days, and then taking this trend develops even have an influence on contemporary history in these islands. So this includes talking on two things: Orientalist role for the emergence of liberalism in the Islamic world, and its influence in the Malay islands.